PELATIHAN TEKNIK CEPENGAN WAYANG KULIT PURWA DI SANGGAR SENI MARDIKA LARAS - Widodo Widodo; Rahma Ari Widihastuti (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
This community service was held to increase the interest of young generation in knowing the art tradition, especially ‘wayang’. Wayang hasknown as the ancient tradition and cannot stand with the other modern art traditions, such as; music or movie. Both of music or movies are still considered as high anticipation of young genertations than wayang itself. The role of ‘dalang’ is prominent in creating the great performance that can be enjoyed by all generations. There are many ways in playing ‘wayang’ in order to make a great performace, one of them is ‘cepengan’. ‘Cepengan’ is the technique of holding ‘wayang’. There are fours variations of ‘cepengan’: (1) ‘Cepengan Methit’, is described like a flying bird. (2) ‘cepengan jagal’ is used to hold animal wayang, (3) ‘cepengan gepok’, is used in playing wayang with big size, like the role of “buta’ or ‘raksasa’, (4) cepengan genu’, is used to play wayang with small size, such as; Arjuna, and Kresna. This community service was held for six months with four meetings. The participant of this community service are elementary school age children with total 17 participants